2020
DOI: 10.26444/aaem/105926
|View full text |Cite
|
Sign up to set email alerts
|

Selenium prevents lithium accumulation and does not disturb basic microelement homeostasis in liver and kidney of rats exposed to lithium

Abstract: prevents lithium accumulation and does not disturb basic microelement homeostasis in liver and kidney of rats exposed to lithium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It inhibits several enzymes, including inositol monophosphatase and glycogen synthase kinase-3 [ 73 ]. However, the ingestion of Li causes many side effects, including hypercalcemia, cardiovascular, and gastrointestinal and parathyroid disorders [ 74 ]. Recent studies demonstrated that Li uptake is associated with reduced tumor incidence, probably through inhibited cell proliferation, which may be linked to reduced DNA replication and S-phase cell cycle arrest [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits several enzymes, including inositol monophosphatase and glycogen synthase kinase-3 [ 73 ]. However, the ingestion of Li causes many side effects, including hypercalcemia, cardiovascular, and gastrointestinal and parathyroid disorders [ 74 ]. Recent studies demonstrated that Li uptake is associated with reduced tumor incidence, probably through inhibited cell proliferation, which may be linked to reduced DNA replication and S-phase cell cycle arrest [ 75 ].…”
Section: Discussionmentioning
confidence: 99%